Human amniotic membrane: a versatile wound dressing. - Gruss, J. S. (1978)
Human amniotic membrane proved to be a versatile and useful temporary biologic dressing in studies involving 120 patients. Wounds, both traumatic and nontraumatic in origin, responded to a protocol that allowed coverage of tissues as diverse as exposed bowel, pleura, pericardium, blood vessels, tendon, nerve and bone. Wounds unresponsive to usual therapeutic measures responded to membrane application. Ease of availability, negligible cost and facilitated wound healing make this temporary biologic dressing generally superior to either cadaver skin allograft or pigskin xenograft. Human amniotic membrane dressings are therefore a useful adjunct in the care of the complicated wound.